INCORPORATING MULTIMEDIA AND TECHNOLOGY TO IMPROVE COMMUNICATION SKILLS AT WTW. INC. JAPAN - Ni Putu Dilia Dewi; Dian Rahmani Putri (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
The key issues with students' communication skills have been found to be extremely low by online learning during the previous two years according to Covid-19. It negatively affects kids' communication abilities. Direct observation is used to identify issues that are evident from the decline in pupils' English communication skills. Online student exchange is the component of the collaboration project with WTW.Inc. Japan that aims to help students' communication abilities. To carry out the activity, students from around the world share knowledge and create presentations utilizing technology tools like multimedia. The desire and motivation of the students to participate in the activity in this study is indicative of the impact that multimedia has on the presentation. Students in the English Club at SMK TI BALI GLOBAL DENPASAR will be the subject of the study. Observations, teacher and student interviews, and questionnaires are all utilized as qualitative research techniques. The Miles and Huberman methods are used to analyze the data, and a pie chart and narrative data presentation were used to illustrate the questionnaire results. The findings of this study demonstrated the significant positive impact of employing multimedia when giving presentations to students from foreign nations.